The Factors Influencing Digital Literacy Practice in Vocational Education: A Structural Equation Modeling Approach - Dwi Jatmoko, Dwi Jatmoko; Suyitno Suyitno, Suyitno Suyitno; Mohamad Sattar Rasul, Mohamad Sattar Rasul; Muhammad Nurtanto, Muhammad Nurtanto; Nur Kholifah, Nur Kholifah; Alias Masek, Alias Masek; Hamid Ramadhan Nur, Hamid Ramadhan Nur (2023)
In the future, vocational students will face all changes and developments in technology and information. In this context, students' digital literacy skills need to be trained to adapt to the demands of the world of work. This article aims to present the results of a study on factors that can improve the digital literacy practice for vocational students as a roadmap for digital learning in the current era. The sampling technique used purposive random sampling of 8 Vocational Schools in East Java Province, Indonesia. The number of respondents in this study amounted to 355 second-year students. The study has found that online learning, motivation, and technology introduction are influenced by students' digital literacy practices, while teacher readiness andb infrastructure must be mediated by online learning. The findings in this study indicate that collaboration from various parties is needed from teachers, school administrators, and policymakers in planning learning that focuses on students' digital abilities.